The Legal Profession in the Era of Digital Capitalism: Disruption or New Dawn? - Salvatore Caserta; Mikael Rask Madsen (Laws, 2019)
This article investigates the impact of what we label “digital capitalism” on the structure and organization of the legal profession. We explore whether the rise of digital capitalism is transforming the dynamics of the legal field by the introduction of new actors and ways of practicing law, which might challenge the traditional control (and monopoly) of jurists on the production of law. We find that not only have new service providers already entered the legal market, but also new on-line tools for solving legal disputes or producing legal documents are gaining a foothold. Similarly, we also find that new intelligent search systems are challenging the role of junior lawyers and paralegals with regard to reviewing large sets of documents. However, big data techniques deployed to predict future courts’ decisions are not yet advanced enough to pose a challenge. Overall, we argue that these developments will not only change legal practices, but are also likely to influence the internal structure and organization of the legal field. In particular, we argue that the processes of change associated with digitalization is further accelerating the economization and commodification of the practice of law, whereby lawyers are decreasingly disinterested brokers in society and defenders of the public good, and increasingly service firms at the cutting edge of the capitalist economy. These developments are also triggering new forms of stratification of the legal field. While some legal actors will likely benefit from digitalization and expand their business, either by integrating new technologies to reach more clients or by developing new niche areas of practices, the more routinized forms of legal practice are facing serious challenges and will most likely be replaced by technology and associated service firms.